Analysis of Compliance, Transparency, and Accountability of The X Party Campaign Fund Report in South Sumatera in The Management of Receipt and Use of Campaign Funds - Singgih Alfiyahya; Tantina Haryati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study analyzes the compliance, transparency, and accountability levels in the campaign finance reports of Party X in South Sumatra, focusing on the management of campaign fund receipts and expenditures. Utilizing a qualitative case study approach, data was gathered through document studies, observation, examination of campaign fund financial reports, and a review of literature on regulations and best practices in campaign fund accountability. Findings indicate efforts toward compliance with existing regulations, yet significant challenges remain in achieving optimal levels of transparency and accountability in campaign fund management. Factors such as insufficient understanding of applicable regulations, lack of awareness regarding the importance of transparency, and complex political pressures and interests often hinder progress. Implications suggest the need for campaign finance reform and increased commitment from stakeholders to enhance integrity and accountability in the political process.